Renal Medullary Carcinoma, A Rare But Aggressive Sickle Cell Nephropathy: A Case Report - Kumar, Lakshmy S; Nair, Vijayalekshmi; Aravindan, K P; Warrier, Narayanankutty (Annals of Pathology and Laboratory Medicine, 2023)
Renal Medullary Carcinoma (RMC) is a highly aggressive cancer that typically affects adults in second to third decades of life with male preponderance and dismal prognosis. As the name indicates, it is medulla centric and is almost exclusively associated with sickle cell hemoglobinopathy. Tumor shows SMARCB1 /INI-1 deficiency and hence called SMARCB1 deficient renal medullary carcinoma. As there are only around 600 cases been reported worldwide till date, we report this case as an eye opener for having high degree of clinical and pathological suspicion in renal cancer patients of younger age, especially if there is no known history of hemoglobinopathy. Prompt diagnosis and treatment is warranted to prolong survival. Our case is that of a 36yr old male who presented with hematuria and loin pain of six months without any significant past history. Radiological evaluation showed right renal mass with extensive metastatic disease. Palliative right radical nephrectomy was done which on thorough histomorphological and immunohistochemical examination was diagnosed as renal medullary carcinoma. Tumor cells showed loss of INI 1 expression which is a surrogate marker for SMARCB1 deficient status. High performance liquid chromatography was done which revealed sickle cell trait. He was started on immunotherapy and chemotherapy, following which he had a favorable treatment response.